A holistic perspective on bank performance using regulation, profitability, and risk-taking with a view on ownership concentration - Shailesh Rastogi; Rajani Gupte; R. Meenakshi (Journal of Risk and Financial Management, 2021)
There is a lack of a holistic perspective on bank performance. This study proposes a multidimensional (three-pronged) approach encompassing regulation, profitability, and nonperforming assets (NPAs) and their interactions as a measure of the performance of a bank. Moreover, the impact of equity holdings of promoters, institutional investors, and retail investors on the proposed three-pronged approach of the bank performance are also explored. Values of the concerned variables were gathered from 2016 to 2019. The dynamic panel data method was applied to empirically test the proposed model. The main findings supported the premises of the proposed approach to bank performance. Furthermore, various ownership classes provided mixed results for their impact on bank performance. Unfavorable roles of promoters and institutional investors and an indifferent role of the retail investors group were startling outcomes of the study. Successful empirical endorsement of the proposed approach for bank performance provides a fresh perspective and has varied policy- and managerial-level implications. The findings regarding various shareholder groups (ownership classes) can be a catalyst to set the policy for ownership distribution in banks, as well as shareholder protection and activism, which are conspicuously absent in India.
Keywords: 330; institutional investors; NPA; ownership; profitability; promoters; regulation; retail investors